SUMMER THUNDER - Shul, Brian, 1948- (Mach 1, Inc., 1993)
Each summer, millions of air show spectators across America and around the world are thrilled to the aerial artistry of the United State Air Force Thunderbirds. Flying fighter jets formation with a precision second to none, the Thunderbirds demonstrate, in breathtaking style, the essence of pride, discipline and teamwork to audiences everywhere